Distribution and abundance patterns of echinoderms in the fjord and channel complex from a subantarctic north Patagonian Ice field, Magellan region - Mutschke, Erika (2017)
The existence of latitudinal marine biodiversity gradients from low to high-southern latitudes is a controversial issue regarding the marine biogeographic division in the Southeastern Pacific. In this region, the Northern Patagonian Icefield is considered a break point for faunistic elements derived from more northern or southern biogeographical realms. However, the division seems to be better defined by distribution patterns and endemism of specific marine taxa. There have been no exhaustive latitudinal benthic inventories compiled along the southern-eastern Pacific Chilean coastline. This study focuses on the spatial distribution variability and relative abundance of the sublittoral echinoderm assemblages and uses them to establish an evaluation of zoogeographic relationship in the Southeastern Pacific and Atlantic Oceans. This is the first time echinoderms have been used for this purpose. A total 3 665 echinoderm specimens were collected in two cruises. Within this organism pool, 29 species were distinguished, belonging to the asteroids (17 species), echinoids (6 species), ophiuroids (4 species) and holothurians (2 species); crinoids were not found. The dominant species were the asteroid Ctenodiscus procurator, the echinoid Pseudechinus magellanicus, the ophiuroid Ophiuroglypha lymani, and the irregular sea urchin Tripylaster philippii. The spatial distribution patterns for the echinoderm clusters along the study area showed only weak geographical trends. Stations belong in three groups: with influence of glacier processes, influence of waters of the open Pacific Ocean, and a third group of stations without any links to specific locations. Rev. Biol. Trop. 65(Suppl. 1): S60-S72. Epub 2017 November 01.